Rancang Bangun Sistem Informasi Manajemen Petra Community Church - Putra, Samuel Hasaja; Nurcahyawati, Vivine; Hananto, Valentinus Roby (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Petra Community Church is a church located on Jalan M.T. Haryono, Semarang. Since January of 2018, it has more than one thousands congregation. Based on their organizational structure, they have head of management and many departments, such as, Ibadah Raya Department, Komsel Department, Pujian Penyembahan Department, and Multimedia  Department. The board is facing a problem about getting data from departements. The data is still scattered in each department and the form is still a flat file (hard-copy). This problem affects the evaluation process of the existing management and also related to the making of annual year work program. Based on this problem, a management information system is needed to be used to process existing data into information, which is useful for decision making by the management of PCC. Management Information System built using the method of the System Development Life Cycle Waterfall model. The waterfall model used is the waterfall model according to Sommerville (2007). This system can handle management requirements related to the availability of master data, and activity data has been carried out up to financial data. Also through this system, the board can monitors activities undertaken by each department.